In vitro Efficacy of Deltamethrin against Hyalomma anatolicum anatolicum - Thakur, Pratibha; Bagherwal, RK; Jayraw, AK; Soni, AK (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Tick and tick-borne diseases such as theileriosis, babesiosis, and Anaplasmosis pose a constant threat to cattle health. Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum are the most commonly found cattle tick species and cause significant economic losses to dairy and leather industries by adversely affecting the milk production and quality of hides